Some stress sensitive parameters of young major carp, Labeo rohita (Hamilton-Buchanan) - Das, Manas K; Das, R K; Mondal, S K (Indian Journal of Fisheries, 2011)
Sress sensitive blood parameters such as haemoglobin, haematocrit, leucocrit,clotting time, plasma chloride, glucose, cholesterol, protein and liver glycogenwere measured in young Labeo rohita reared in earthen ponds and laboratorytanks. No significant correlation was obtained between the blood parametersand environmental factors. The interactions between pond and age was significantfor most of the parameters. There was no significant differences amongages for all the characteristics. The range of mean values obtained for the differentblood characteristics were within a narrow range and can serve as normallevels for Labeo rohita blood, reared under similar set of conditions. It issuggested that the normal values can be used as a guideline to monitor impactof fish disease and environmental stressors in Indian major carps.